What your faculty need to known about open access publishing - JACQUELINE KRESS (Academic Chairpersons Conference Proceedings, 2018)
Scholarly publication is a factor in faculty evaluation. Online journals–open access (OA) and traditional—are now available. Views about OA journals are often controversial, and have even affected tenure and promotion decisions. This session reviews facts about OA and provides exemplar materials to use to review/revise your publication policies.
Keywords: Scholarship; open-access journals; predatory publishers; rank-and-tenure decisions; personnel decisions; scholarship standards; scholarship policies